Strategy For Developing Palm Sugar Business In Lebong Regency - Mursana; Susanti, Neri; Irwanto, Tito (Universitas Dehasen Bengkulu, 2025)
The purpose of the study was to determine the strategy for developing the palm sugar business in Lebong Regency. The sample in this study was 45 people consisting of 5 employees of the Tebo Lai Palm Sugar Business, Lebong Regency for internal factors and 40 people for external factors, namely customers of the Tebo Lai Palm Sugar Business, Lebong Regency. The analysis method used was a SWOT analysis consisting of the Internal Strategy Factor Matrix (IFAS) and the External Strategy Factor Matrix (EFAS). The results showed that the strategy of the Tebo Lai Palm Sugar Business, Lebong Regency supports an aggressive strategy, or SO strategy in the SWOT matrix. The result of the addition of the strengths owned is 18.75 while the weaknesses are 11.73, so the internal factor quadrant is 18.75 - 11.73 = 7.02, meaning the ability of the Tebo Lai Palm Sugar Business, Lebong Regency to utilize strengths and minimize weaknesses that exist internally. The opportunities owned from this strategy are 17.59 and threats are 11.03. So the external factor quadrant is 17.59 - 11.03 = 6.55, meaning the high ability of the Tebo Lai Palm Sugar Business, Lebong Regency, in utilizing opportunities and overcoming threats faced by the company in marketing the ground coffee business. If the two weighted values ​​are combined in the IE matrix, then both will meet in cell I, which supports an aggressive strategy.